Penerapan Spiritual Capital Dalam Sistem Tata Kelola Keuangan Usaha, Mikro, Kecil, dan Menengah: Studi Pada Usaha Upakara Yadnya di Desa Sangeh - I Gusti Ayu Putu Winda Sri Anggreni; Cokorda Gde Bayu Putra; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2026)
This study aims to analyze the application of spiritual capital in the financial governance system of Micro, Small, and Medium Enterprises (MSMEs) performing yadnya ceremonies in Sangeh Village. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation of yadnya ceremony business owners. Data validity was tested using source triangulation and technical triangulation techniques. The results of the study indicate that business financial governance is still carried out simply and has not implemented a formal accounting system, but has included aspects of planning, recording, and control. Planning is carried out through estimating material needs and determining selling prices, recording is done manually, and control is carried out by prioritizing the fulfillment of operational obligations. The application of spiritual capital in business financial governance is reflected in the values ​​of honesty, integrity, responsibility, and empathy. These values ​​are seen in the transparency of financial records, consistency in fulfilling obligations to employees, responsibility in business management, and concern for customers. Thus, spiritual values ​​play an important role in shaping financial governance practices that are not only oriented towards profit, but also on moral and social values.